Pengaruh Kompetensi Personel dan Kemampuan Dock Fasharkan Terhadap Kesiapan Unsur KRI PRX - Kristanto, Vendri; Sugiarto, Budi; Wiratama, Eska Yosep; Susilo, A.K. (Jayapangus Press, 2024)
In the context of maritime defense, the readiness of fleet elements is a very vital factor. Fleet Command II (Koarmada II), as one of the main commands in the structure of the Indonesian Navy, has a crucial responsibility to ensure that all elements of its warships are always ready to carry out various maritime operations. This operational readiness is not only determined by the physical condition of the warship, but also depends heavily on two main factors personnel competence in this case KRI personnel and the capability of the Fasharkan Surabaya dock. The purpose of this study was to analyze the effect of personnel competence and Fasharkan dock capability on the operational readiness of elements. The method used is a quantitative method with the help of SPSS version 26 software, with a questionnaire via Google Form with Random sampling used to collect sample data. The results of the study showed a strong correlation between KRI PRX Personnel Competence and Surabaya Fasharkan Dock Capability on Element Readiness in the Koarmada II environment. KRI PRX Personnel Competence and Surabaya Fasharkan Dock Capability partially have a very strong and positive relationship and have a significant influence on element readiness. This can be interpreted that the better the competence of KRI PRX personnel and the capabilities of the Fasharkan dock, the higher the readiness of elements in the Koarmada II.